2018
DOI: 10.1007/s10157-018-1619-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of the significance of immunofluorescent findings on clinicopathological features in IgA nephropathy

Abstract: We found the different roles of glomerular immune reactants' deposition in the inflammatory process from acute to chronic stage. IgA deposition together with IgG, Fib and C3 may produce acute inflammatory injury. IgM deposition might occur in the early stage of inflammation and remains until late sclerotic stage. The prominent deposition of IgA related to low risk for ESRD in patients who received steroids might suggest effectiveness of steroids in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 33 publications
3
22
0
1
Order By: Relevance
“…[22][23][24] We checked the impact of glomerular C3 deposition on IgAN in recent years, and our findings are shown in Table S1. [25][26][27][28][29][30][31] In this study, we also found that patients with intense glomerular C3 deposition also had glomerular IgA, IgM, and IgG deposition. This suggests that the complement alternative pathway is associated with immune complex deposition in the glomerulus.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[22][23][24] We checked the impact of glomerular C3 deposition on IgAN in recent years, and our findings are shown in Table S1. [25][26][27][28][29][30][31] In this study, we also found that patients with intense glomerular C3 deposition also had glomerular IgA, IgM, and IgG deposition. This suggests that the complement alternative pathway is associated with immune complex deposition in the glomerulus.…”
Section: Discussionsupporting
confidence: 75%
“…Many studies have previously shown that glomerular C3 deposition and complement activation are involved in the pathogenesis of patients with various kidney diseases, including lupus nephritis, 19 C3 glomerulopathy, 20 antineutrophil cytoplasmic antibody‐mediated crescentic glomerulonephritis, 21 and IgAN 22–24 . We checked the impact of glomerular C3 deposition on IgAN in recent years, and our findings are shown in Table 25–31 . In this study, we also found that patients with intense glomerular C3 deposition also had glomerular IgA, IgM, and IgG deposition.…”
Section: Discussionsupporting
confidence: 66%
“…After we have provided evidence that Gd-IgA1 is deposited at vessels of systemic and skin-limited IgAV, we believe it is reasonable to extrapolate the IgAN multi-hit hypothesis [25][26][27][28] to IgAV as shown in Figure 3. We detected co-deposition of IgG (as in IgAN) in 2 cases of skin-limited IgAV consistent with the presence of IgA-IgG immune complexes [29]. In those cases with no IgG codeposition it is likely that these patients developed IgA1 autoantibodies to GD-IgA1 (as has been described in IgAN) which cannot be definitively identified with current staining techniques.…”
Section: Accepted Manuscriptsupporting
confidence: 72%
“…Hallmarks of classical pathway activation, such as C1q, are usually not detected in the glomeruli of patients with IgAN (57), although it may be found in biopsies with advanced glomerulosclerosis (72). Therefore, the presence of glomerular C4d in IgAN suggests activation of the lectin pathway rather than the classical pathway.…”
Section: Complement Proteins and Complement Fragments In Pathologymentioning
confidence: 99%